Discovery of single nucleotide polymorphism in Gossypium hirsutum and G. barbadense through next generation sequencing approach - Sudakara, Reddy S.; Katageri, I. S.; Kumar, N. V. Mohan; Jadhav, M. P.; Adiger, Sateesh; Chakravartty, Navajeet; Vamadevaiah, H. M.; Reddy, V. B. (The Indian Journal of Genetics and Plant Breeding, 2017)
Single nucleotide polymorphism was identified using ddRAD and pooled amplicon sequencing between the allotetraploid cotton genotypes of G. hirsutum var. DS-28 (POOL-H) and G. barbadense var. SBYF-425 (POOL-B). The 471270 (470161 SNP and 1109 INDELs), 2723 (2621 SNP and 102 INDELs) and 780 (759 SNP and 21 INDELs) variant calling were predicted at read depth of 10 in the genotypes by using G. raimondii (D5), G. arboreum (A2) and G. hirsutum (AD) as reference genomes, respectively. Further, filtered out false positive homoeologous SNPs between parents (DS-28 and SBYF-425) at read depth of 10, identified 245 and 45 homozygous polymorphic SNPs between parents based on pooled amplicon sequencing and ddRAD sequencing by using G. raimondii, G. arboreum and G. hirsutum as a reference genomes. Based on gene function, 5 SNPs were converted into KASPar markers and genotyped in 21 RILs for fibre quality traits. Identified polymorphic SNPs and INDELs can be used for genotyping and QTL mapping after converting into functional markers.